Training rugby athletes with an external attentional focus promotes more automatic adaptions in landing forces - Widenhoefer, T. L.; Miller, T. M.; Weigand, M. S.; Watkins, E. A.; Almonroeder, T. G. (Sports Biomechanics, 2019)
Training to reduce landing forces is a common component of anterior cruciate ligament injury prevention programmes. The purpose of this study was to compare the effects of training incorporating instructions promoting an internal versus external attentional focus on landing forces in adolescent rugby athletes. Twenty-two rugby athletes were randomly allocated to groups that received instructions promoting an internal versus an external focus during a two week training programme. Landing forces were recorded before and after completion of the programme. During follow-up testing, landings were performed with and without a secondary cognitive task. Both groups exhibited a similar reduction in landing forces following training for trials performed without the secondary cognitive task. However, the groups responded differently when the secondary cognitive task was imposed. Athletes who were trained with an internal focus demonstrated a prominent increase in landing forces for trials that included the secondary cognitive task (vs. trials performed without the secondary cognitive task), whereas the secondary cognitive task had minimal influence for athletes who were trained with an external focus. It appears that training with an external focus may promote adaptations in landing mechanics that can be implemented more automatically.